Biogeography of planktonic and benthic cyanobacteria in coastal waters of the Big Island, Hawai'i. Issue 1 (29th April 2014) - Chamberlain, Samuel D.; Kaplan, Katherine A.; Modanu, Maria; Sirianni, Katherine M.; Annandale, Senifa; Hewson, Ian
Abstract Cyanobacteria are biogeochemically significant constituents of coral reef ecosystems; however, little is known about biotic and abiotic factors influencing the abundance and composition of cyanobacterial communities in fringing coral reef waters. To understand the patterns of cyanobacterial biogeography in relation to coastal environmental factors, we examined the diversity of planktonic and benthic cyanobacteria at 12 sites along the west coast of Hawaii's Big Island. We found distinct cyanobacterial communities in sediments compared to the water column. In both sediments and water, community structure was strongly related to overall biomass (chlorophyll a concentration), although both these communities corresponded to different sets of biotic/abiotic variables. To examine the influence of freshwater input on planktonic cyanobacterial communities, we conducted a mesocosm experiment where seawater was amended with freshwater from two sources representing high‐ and low‐human population influence. Planktonic cyanobacterial abundance decreased over time in mesocosms, although chlorophyll a concentration significantly increased with time, indicating cyanobacteria were likely outcompeted by other phytoplankton in incubations. Our results show that cyanobacterial community structure may be affected by runoff from terrestrial habitats, but that the composition of cyanobacterial communities inhabiting these locations is also structured by factors not measured in this study.